The bony horncore of the common eland (Taurotragus oryx): composition and mechanical properties of a spiral fighting structure. Issue 1 (10th October 2017) - Cappelli, Jamil; García, Andrés J.; Kotrba, Radim; Gambín Pozo, Pablo; Landete‐Castillejos, Tomas; Gallego, Laureano; Ceacero, Francisco
Abstract: Horns are permanent structures projecting from the head of bovids, consisting of a bony horncore covered with a layer of skin and then a sheath of keratinous material showing variability of growth intensity based on nutrition. From the point of view of the horn's mechanical properties, the keratin sheath has been widely studied, but only a few studies have considered the complete structure of the horn and fewer studies have focused on the bony horncore and its characteristics. The latter showed the important role of the bony core, when cranial appendages are subject to mechanical stress (as happens during fighting). The mechanical properties of bone material, along with its mineral profile, are also important, because they can show effects of different factors, such as nutrition and mineral deficiencies in diet. For this reason, eight horncores of captive common eland male were sampled at four positions along the vertical axis of the horn. The main aim was to study variation in mechanical properties and the mineral content along the vertical axis of the horncores. We further analysed whether the spiral bony ridge present on eland horncores differs in any of the studied properties from adjacent parts of the horncore. In other antelopes, spiral ridges on the horns have been proposed to increase grip during wrestling between males. Cross‐sections of the horncores were performed at four positions along the longitudinal axis and, for each position, two bone bars were extracted to be tested in impact and bending. Moreover, in the first sampling position (the closest position to the base) two bars were extracted from the spiralled bony area. The resulting fragments were used to measure ash content, bone density and mineral content. Results showed that horn bone decreased along the vertical axis, in ash (−36%), density (−32%), and in impact work ' U ' (marginally significant but large effect: −48%). The concentration of several minerals decreased significantly (Mg, Cr, Mn and Tl by −33%, −25%, −31%, −43%, respectively) between the basal and the uppermost sampling site. The bone tissue of the horncore spiral compared with non‐spiral bone of the same position showed a lower ash content (53% vs. 57%), Mg and Mn; in addition to showing approximately half values in work to peak force ' W ', bending strength ' BS ' and ' U ', but not in Young's modulus of elasticity ' E '. In conclusion, similarly to the results in a totally different fighting bony structure, the antlers, the horncore of eland shows advantageous parameters in bone tissue of the base in respect to the tip, with higher values for mechanical properties, density and mineral profile. Moreover, the spiral bone tissue showed lower material mechanical properties. Probably the spiral tissue of the horn may have a role in deflecting potential cross‐sectional fractures during wrestling. In addition, it may serve to improve the grip during wrestling, and we propose that it may also prevent risk of rotation of sheath with respect to internal bone not only in this, but also in other straight bovid horns.